2013
DOI: 10.1088/0031-9155/58/17/5997
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic redesign of the HYPERcollar applicator: toward improved deep local head-and-neck hyperthermia

Abstract: Accumulating evidence shows that hyperthermia improves head-and-neck cancer treatment. Over the last decade, we introduced a radiofrequency applicator, named HYPERcollar, which enables local heating also of deep locations in this region. Based on clinical experience, we redesigned the HYPERcollar for improved comfort, reproducibility and operator handling. In the current study, we analyze the redesign from an electromagnetic point of view. We show that a higher number of antennas and their repositioning allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 27 publications
1
68
0
Order By: Relevance
“…They utilize the constructive wave interference from a set of antennas at the tumor site [5][6][7][8]. The parameters that determine the system's ability to focus are the phases and amplitudes of the excitation of antennas in the phased array.…”
Section: Introductionmentioning
confidence: 99%
“…They utilize the constructive wave interference from a set of antennas at the tumor site [5][6][7][8]. The parameters that determine the system's ability to focus are the phases and amplitudes of the excitation of antennas in the phased array.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the potential of using microwave hyperthermia for the treatment of malignancies in head, neck and chest regions [19], [36][37][38][39][40][41][42] has been clinically tested [43,44]. For microwave hyperthermia to be successful in treating cancer, tumours are heated to a moderate temperature while keeping healthy tissue at normal body temperature.…”
Section: Thermal Therapy In Cancer Treatmentmentioning
confidence: 99%
“…According to [43], the hot spot to target specific absorption ratio (SAR) quotient (HTQ) can be used to avoid undesired heating in healthy tissue. It was concluded that if HTQ is less than 1, the resulted temperature induced in the tumour is always higher than other areas.…”
Section: Define Fitness Functionmentioning
confidence: 99%
See 2 more Smart Citations